The Elephant of Belfast : a novel - Walsh, S. Kirk (Berkeley, California : Counterpoint Press, 2020)
"The Elephant of Belfast chronicles a seven-month period of time when the Germans unexpectedly bombed Belfast, Northern Ireland, also known as the Belfast Blitz. Through the lens of the Bellevue Zoo and one of its zookeepers, twenty-year-old Hettie Quin, the novel animates how the war irrevocably impacted-and shaped the lives of Belfast's citizens in broad and intimate ways. In October 1940, Hettie meets Violet, a three-year-old Asian elephant arriving at the Belfast docks from Ceylon. Soon, she becomes Violet's dedicated zookeeper at the Bellevue Zoo. At the same time, Hettie continues to experience the grief related to the recent loss of her beloved older sister, Anna, and the abandonment of her father, Thomas, who left her mother, Rose. On April 15th , 1941, Belfast is attacked for five hours, with 674 bombs falling, and almost a thousand civilians being killed. During the bombings and its aftermath, Hettie does all that she can to save her elephant, and survive the destruction and escalating sectarian unrest of the city. Even though Hettie is still only twenty years old by the novel's end, she's aged at least a decade, her life and perspective transforming in tragic and unexpected ways. Taken altogether, The Elephant of Belfast reflects a complicated portrait of loss, grief, love, and resilience, and how the zoo and the city of Belfast suffered during these catastrophic attacks. At the narrative's heart is a changing relationship between a young woman and an elephant: At first, it seems that Hettie saves Violet, but in the end, Violet saves her"--.
Keywords: Belfast (Northern Ireland) -- History -- Bombardment, 1941 -- Fiction; Historical fiction